Pelatihan Penyusunan Laporan Keuangan Secara Sederhana Pada Paguyuban Grand Viona Kuripan Ciseeng Bogor : Pelatihan Penyusunan Laporan Keuangan Secara Sederhana Pada Paguyuban Grand Viona Kuripan Ciseeng Bogor - Rizka Wahyuni Amelia; Hasanudin; Lina Nofiana (Abdi Jurnal Publikasi, 2023)
The purpose of holding this Community Service activity is to provide training in preparing financial reports for residents of the Grand Viona Kuripan Ciseeng Bogor Community Association. The method used in this Community Service is in the form of group discussions and direct practice in preparing simple financial reports. This counseling educates residents of the Grand Viona Kuripan Ciseeng Bogor Community Association on the use of financial reports for small and large scale businesses. The result of the activity is that residents of the Grand Viona Kuripan Ciseeng Bogor Association can directly create simple financial reports for business, and these simple financial reports can be used as consideration in making business decisions.